A study on the effect of using different type of organic acid on the pre-treatment of extraction silica from rice husk ash (RHA): article - Charles, Hanearytha Litad; Ali, Sherif Abdulbari (2017)
Rice husk is an abundant agricultural byproduct, which contain high amount of silica which is about 60% and can be made into raw materials that can produce silica gel and powders. There are abundant uses of silica which are for the glass production, adsorbent, cleansing agent and others. Synthesis was done by using different acids namely, acetic acid, citric acid, and formic acid. The sample was collected from rice mill that located in Sabah. The proximate analysis of the sample was determined the moisture content, volatile matter, fixed carbon and ash by using the thermobalance TGA/SDRA51e according to ASTM D5142-02a. The percentage of the silica being extracted was being compared to the previous research. The characterization of the silica obtained determined by the Fourier Transform Infrared Spectrograph (FTIR) and the surface area were analyzed by using BET surface area instrument. In this research, the variation concentration of organic acid that was used for the pre-treatment of the RHA was not being concerned. It was found that, using inorganic acid at the pre-treatment will give higher yield of silica from RHA. The percentage of silica that was extracted with the pre-treatment of acetic acid, formic acid, and oxalic acid are 38.97 %, 36.14 % and 37.27 % respectively.